Sodium vanadium fluorophosphate-based sodium ion battery positive electrode material and preparation method thereof

Through the sol-gel method and high-temperature solid phase sintering reaction, combined with the esterification graft modification of the regulator, a high-purity sodium vanadium fluorophosphate positive electrode material was prepared, which solved the problem of low-voltage discharge platform caused by the miscellaneous phases in the existing materials and improved the energy density and cycle stability of the battery.

CN119018872BActive Publication Date: 2025-03-11SHANDONG DINGTENG NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410966285.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-03-11
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

The existing sodium fluorine vanadium phosphate materials contain miscellaneous phases such as vanadium phosphate and other vanadium compounds, resulting in a low voltage discharge platform in the charge and discharge curve of the material, reducing the energy density of the battery.

Method used

The sol-gel method and high-temperature solid phase sintering reaction were used to prepare a high-purity sodium vanadium fluorophosphate positive electrode material through esterification and graft modification of the regulator to avoid the occurrence of miscellaneous phases.

Benefits of technology

The low voltage discharge platform is eliminated, and the working voltage and energy density of the sodium vanadium fluorophosphate positive electrode material is improved, which enhances the cycling stability and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material and a preparation method thereof, and relates to the technical field of battery materials. The preparation method of the sodium vanadium fluorophosphate-based sodium ion battery positive electrode material of the invention comprises the following steps: adding a carbon source, a vanadium source, a phosphorus source, a fluorine source, a sodium source, and deionized water into a reactor and stirring to obtain a gel A; heating the gel A to remove water, vacuum drying, and grinding to obtain a precursor; pre-sintering the precursor in an inert gas atmosphere, secondary sintering, and furnace cooling to obtain the sodium vanadium fluorophosphate-based sodium ion battery positive electrode material. The invention is simple to operate and has good reproducibility. The prepared material has a high energy density and excellent rate and cycle performance, and can meet the needs of practical applications of sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery materials, and in particular to a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] Sodium is cheap and abundant in reserves. The research and development and application of sodium-ion batteries are conducive to promoting the development and innovation of large-scale energy storage technology. In terms of composition, the positive electrode material is a key part of the sodium-ion battery, which largely determines the electrochemical properties of the entire battery system, such as capacity, operating voltage, and cycle life. In the existing research on positive electrode materials for sodium-ion batteries, the polyanionic compound sodium vanadium fluorophosphate (chemical formula Na3V2(PO4)2F3) has a large number of sodium storage vacancies and unobstructed sodium ion diffusion channels due to its empty three-dimensional skeleton structure, which makes it have a higher specific capacity and better cycle stability as a positive electrode material for sodium-ion batteries.

[0003] Sodium vanadium fluorophosphate has great application prospects as a positive electrode material for commercial sodium-ion batteries, and therefore has received widespread attention. Although sodium vanadium fluorophosphate, a positive electrode material for sodium-ion batteries, has the above advantages, most of the sodium vanadium fluorophosphate samples prepared in current studies and reports contain impurities such as sodium vanadium phosphate and other vanadium compounds. The presence of impurities will directly reduce the discharge capacity of the positive electrode material on the one hand, and on the other hand will also reduce the average operating voltage that the positive electrode can exhibit to a certain extent, thereby reducing the energy density of the battery. Most literature reports that the sodium vanadium fluorophosphate samples they prepared have a charge and discharge curve that shows 3.6V (vs.Na + / Na) and 4.1V (vs.Na + / Na) and there are two discharge voltage platforms, 3.3V (vs.Na + / Na), which is the embodiment of the sodium vanadium phosphate hybrid phase. Therefore, in order to achieve higher energy density and better performance, a simple synthetic method is needed to prepare sodium vanadium fluorophosphate, a positive electrode material for sodium ion batteries. Summary of the invention

[0004] The purpose of the present invention is to provide a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material and a preparation method thereof, to solve the following technical problems:

[0005] The sodium vanadium fluorophosphate material prepared by the existing method contains impurities such as sodium vanadium phosphate and other vanadium compounds, which results in the material showing a 3.6V (vs. Na + / Na) and 4.1V (vs.Na + / Na) and 3.3V (vs.Na + / Na) of the low voltage discharge platform.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material comprises the following steps:

[0008] S1: Add a carbon source, a vanadium source, deionized water, and a regulator into a reaction bottle and stir once, then add a phosphorus source, a fluorine source, and a sodium source and stir twice to obtain gel A;

[0009] S2: heating gel A to remove water, vacuum drying, and grinding to obtain a precursor;

[0010] S3: pre-sintering, secondary sintering, and furnace cooling the precursor in an inert gas atmosphere to obtain a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material;

[0011] The preparation method of the regulator comprises the following steps:

[0012] A1: Add calcium lignin sulfonate, deionized water and maleic anhydride into a reaction kettle and disperse them evenly, adjust the pH to 10-11, control the temperature to 60-80°C, keep the reaction for 1-3h, precipitate, wash and dry to obtain component 1;

[0013] A2: In a nitrogen atmosphere, component 1, thionyl chloride and N,N'-dimethylbenzoyl are added to a reaction bottle and dispersed evenly, refluxed for 18-24 hours, thionyl chloride is removed by vacuum distillation, washed and dried to obtain component 2;

[0014] A3: In a nitrogen atmosphere, add diethylenetetramine and triethylenetetramine into a reaction bottle, control the temperature at 120-130°C, keep the reaction warm for 24-36 hours, remove triethylenetetramine by vacuum distillation, filter, wash and dry to obtain a regulator.

[0015] As a further solution of the present invention: the addition ratio of calcium lignin sulfonate, deionized water and maleic anhydride in A1 is 10 g: 100-500 mL: 6-10 g.

[0016] As a further solution of the present invention: the addition ratio of component 1, thionyl chloride and N,N'-dimethylbenzoyl in A2 is 1g:100-200mL:10-20mL.

[0017] As a further solution of the present invention: the addition ratio of 0.5 g of component 2 and 120 mL of triethylenetetramine in A3 is 1 g: 20-100 mL.

[0018] As a further solution of the present invention: the vanadium source is vanadium pentoxide, sodium metavanadate, ammonium metavanadate; the carbon source is oxalic acid; the phosphorus source is ammonium dihydrogen phosphate; the sodium source is sodium fluoride; and the fluorine source is sodium fluoride.

[0019] As a further embodiment of the present invention: the molar ratio of vanadium, phosphorus, fluorine and sodium in gel A is (2-2.5):2:3:(3-6); the molar ratio of carbon source to vanadium source is 2-4:1; the concentration of vanadium in solution A is 0.2-1 mol / L; and the additive accounts for 1-5% of the total mass of gel A.

[0020] As a further solution of the present invention: the specific steps of the first stirring in S1 are: controlling the temperature at 70-90°C and stirring until a grass green color appears; the specific steps of the second stirring are: controlling the temperature at 80-90°C and stirring until the solution becomes a gel.

[0021] As a further solution of the present invention: the specific steps of pre-sintering in S3 are: controlling the heating rate to 5°C / min, heating to 350-450°C, and pre-sintering for 3-5h; the specific steps of secondary sintering in S3 are: controlling the heating rate to 5°C / min, heating to 700-800°C, and secondary sintering for 4-8h.

[0022] A sodium vanadium fluorophosphate-based sodium ion battery positive electrode material, prepared by any one of the above preparation methods.

[0023] Beneficial effects of the present invention:

[0024] The present invention first uses calcium lignin sulfonate as a raw material and maleic anhydride as a modifier for esterification grafting modification to obtain component one; and uses thionyl chloride to chlorinate the carboxyl group on component one to obtain component two; finally, triethylenetetramine is used to graft the acyl chloride group on component two to obtain a regulator. The regulator prepared in this application is added together with oxalic acid as a synergistic carbon source in the preparation process of sodium vanadium fluorophosphate-based sodium ion battery positive electrode materials; the regulator can not only adjust the pH of the precursor solution through its own pH buffering effect, effectively reducing the escape of fluorine elements in the subsequent material during the calcination process; and the Ca element and the fluorine element contained in the regulator generate CaF2 that is not easy to decompose at high temperature during the sintering process, effectively avoiding the escape of F, reducing the generation of impurities, and improving the electrochemical properties of the material.

[0025] The regulator prepared in this application is used in combination with oxalic acid to make the prepared sodium vanadium fluorophosphate-based sodium ion battery positive electrode material particles evenly distributed and fine, effectively reducing the sodium ion migration path and improving the electrochemical performance of the sodium vanadium fluorophosphate composite material. This application prepares a high-purity sodium vanadium fluorophosphate positive electrode material for sodium ion batteries through a sol-gel method and a high-temperature solid-phase sintering reaction, eliminating the low operating voltage platform of about 3.3V (vs. Na+ / Na) caused by the impurity phase, and improving the operating voltage and energy density of this positive electrode material. DETAILED DESCRIPTION

[0026] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] The preparation method of the regulator comprises the following steps:

[0029] A1: 10 g of calcium lignin sulfonate, 100 mL of deionized water, and 6 g of maleic anhydride were added to a reaction kettle and dispersed evenly, 40 wt % of sodium hydroxide aqueous solution was added to adjust the pH to 10, the temperature was controlled at 60°C, the reaction was kept warm for 1 h, 30 wt % of dilute sulfuric acid was added for precipitation, washed, and dried to obtain component 1;

[0030] A2: In a nitrogen atmosphere, 10 g of component 1, 1000 mL of thionyl chloride, and 100 mL of N,N'-dimethylbenzoyl were added to a reaction bottle and dispersed evenly. The mixture was refluxed for 18 h, and the thionyl chloride was removed by vacuum distillation, washed, and dried to obtain component 2.

[0031] A3: In a nitrogen atmosphere, add 10 g of component 2 and 200 mL of triethylenetetramine into a reaction bottle, control the temperature to 120°C, keep the reaction warm for 24 hours, remove the triethylenetetramine by vacuum distillation, filter, wash and dry to obtain a regulator.

[0032] Example 2

[0033] The preparation method of the regulator comprises the following steps:

[0034] A1: 10 g of calcium lignin sulfonate, 300 mL of deionized water, and 8 g of maleic anhydride were added to a reaction kettle and dispersed evenly. A 40 wt % aqueous sodium hydroxide solution was added to adjust the pH to 10. The temperature was controlled at 70°C and the reaction was kept warm for 2 h. 30 wt % dilute sulfuric acid was added for precipitation, washed, and dried to obtain component 1.

[0035] A2: In a nitrogen atmosphere, 10 g of component 1, 1500 mL of thionyl chloride, and 150 mL of N,N'-dimethylbenzoyl were added to a reaction bottle and dispersed evenly. The mixture was refluxed for 21 h, and the thionyl chloride was removed by vacuum distillation, washed, and dried to obtain component 2.

[0036] A3: In a nitrogen atmosphere, add 10 g of component 2 and 600 mL of triethylenetetramine into a reaction bottle, control the temperature to 125°C, keep the reaction warm for 30 hours, remove the triethylenetetramine by vacuum distillation, filter, wash and dry to obtain a regulator.

[0037] Example 3

[0038] The preparation method of the regulator comprises the following steps:

[0039] A1: 10 g of calcium lignin sulfonate, 500 mL of deionized water, and 10 g of maleic anhydride were added to a reaction kettle and dispersed evenly, 40 wt % of sodium hydroxide aqueous solution was added to adjust the pH to 11, the temperature was controlled at 80°C, and the reaction was kept warm for 3 h, 30 wt % of dilute sulfuric acid was added for precipitation, washed, and dried to obtain component 1;

[0040] A2: In a nitrogen atmosphere, 10 g of component 1, 2000 mL of thionyl chloride, and 200 mL of N,N'-dimethylbenzoyl were added to a reaction bottle and dispersed evenly. The mixture was refluxed for 24 h, and the thionyl chloride was removed by vacuum distillation, washed, and dried to obtain component 2.

[0041] A3: In a nitrogen atmosphere, 10 g of component 2 and 1000 mL of triethylenetetramine were added to a reaction bottle, the temperature was controlled at 130°C, the reaction was kept warm for 36 hours, the triethylenetetramine was removed by vacuum distillation, and the reaction was performed by filtration, washing and drying to obtain a regulator.

[0042] Example 4

[0043] A method for preparing a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material comprises the following steps:

[0044] S1: Add 270.1g oxalic acid, 182g vanadium pentoxide, deionized water, and the regulator prepared in Example 1 into a reaction bottle, control the temperature at 70-90°C, and stir until a grass green color appears, add 230g diammonium phosphate and 125.9g sodium fluoride, control the temperature at 80-90°C, and stir until the solution becomes a gel, to obtain gel A; wherein the admixture accounts for 3% of the total mass of gel A;

[0045] S2: heating gel A to remove water, vacuum drying, and grinding to obtain a precursor;

[0046] S3: In an inert gas atmosphere, the precursor is heated to 350°C at a rate of 5°C / min, and pre-sintered for 5 hours; the precursor is heated to 800°C at a rate of 5°C / min, and secondary sintered for 4 hours. The precursor is cooled in the furnace to obtain a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material.

[0047] The electrochemical performance of the material prepared in Example 4 was tested, wherein the charge-discharge curve showed 3.7V (vs. Na + / Na)、4.0V(vs.Na + / Na) two potential platforms.

[0048] Example 5

[0049] Compared with Example 4, Example 5 is just that the regulator prepared in Example 1 added in Example 4 is replaced by the regulator prepared in Example 2 in equal amount, and its components and preparation method are completely consistent with those of Example 4.

[0050] The electrochemical performance of the material prepared in Example 5 was tested, wherein the charge-discharge curve showed 3.7V (vs. Na + / Na)、4.2V(vs.Na + / Na) two potential platforms.

[0051] Example 6

[0052] Compared with Example 4, Example 6 is just that the regulator prepared in Example 1 added in Example 4 is replaced by the regulator prepared in Example 3 in equal amount, and its components and preparation method are completely consistent with those of Example 4.

[0053] The electrochemical performance of the material prepared in Example 6 was tested, wherein the charge-discharge curve showed 3.6V (vs. Na + / Na)、4.1V(vs.Na + / Na) two potential platforms.

[0054] Comparative Example 1

[0055] The preparation method of the regulator comprises the following steps:

[0056] A1: 10 g of calcium lignin sulfonate, 300 mL of deionized water, and 8 g of maleic anhydride were added to a reactor and dispersed evenly. A 40 wt % aqueous sodium hydroxide solution was added to adjust the pH to 10. The temperature was controlled at 70° C. and the reaction was kept warm for 2 h. 30 wt % dilute sulfuric acid was added for precipitation, washed, and dried to obtain a regulator.

[0057] Comparative Example 2

[0058] The preparation method of the regulator comprises the following steps:

[0059] A1: 10 g of calcium lignin sulfonate, 300 mL of deionized water, and 8 g of maleic anhydride were added to a reaction kettle and dispersed evenly. A 40 wt % aqueous sodium hydroxide solution was added to adjust the pH to 10. The temperature was controlled at 70°C and the reaction was kept warm for 2 h. 30 wt % dilute sulfuric acid was added for precipitation, washed, and dried to obtain component 1.

[0060] A2: In a nitrogen atmosphere, 10 g of component 1, 1500 mL of thionyl chloride and 150 mL of N,N'-dimethylbenzoyl were added to a reaction bottle and dispersed evenly. The mixture was refluxed for 21 h. The thionyl chloride was removed by vacuum distillation, washed and dried to obtain a regulator.

[0061] Comparative Example 3

[0062] Compared with Example 4, Comparative Example 3 is that only the regulator prepared in Example 1 added in Example 4 is replaced by lignin in an equal amount, and its components and preparation method are completely consistent with those of Example 4.

[0063] The electrochemical performance of the material prepared in Comparative Example 3 was tested, wherein the charge-discharge curve showed 3.6V (vs. Na + / Na)、4.1V(vs.Na + / Na)、3.3V(vs.Na + / Na) three potential platforms.

[0064] Comparative Example 4

[0065] Compared with Example 4, Comparative Example 4 is that only the regulator prepared in Example 1 added in Example 4 is replaced by an equal amount of the regulator prepared in Comparative Example 1, and its components and preparation method are completely consistent with those of Example 4.

[0066] The electrochemical performance of the material prepared in Comparative Example 4 was tested, wherein the charge-discharge curve showed 3.7V (vs. Na + / Na)、4.1V(vs.Na + / Na) two potential platforms.

[0067] Comparative Example 5

[0068] Compared with Example 4, Comparative Example 5 is that only the regulator prepared in Example 1 added in Example 4 is replaced by the regulator prepared in Comparative Example 2 in equal amount, and its components and preparation method are completely consistent with those of Example 4.

[0069] The electrochemical performance of the material prepared in Comparative Example 5 was tested, wherein the charge-discharge curve showed 3.7V (vs. Na + / Na)、4.1V(vs.Na + / Na) two potential platforms.

[0070] Performance Testing

[0071] Prepare the battery:

[0072] ① Preparation of pole pieces: The positive electrode materials sodium vanadium phosphate prepared in Examples 4-6 and Comparative Examples 3-5 in a mass ratio of 70:20:10 were fully ground with acetylene black and PTFE, mixed evenly, and N-methylpyrrolidone was added as a dispersant to grind and mix to obtain a paste, and the paste was evenly coated on the current collector aluminum foil with a scraper, placed in a vacuum drying oven at 120°C and dried for 12h, and then punched into a positive electrode disc with a diameter of 12mm at 10MPa as a positive electrode;

[0073] ②Prepare the electrolyte: use 1 mol / L NaClO4 organic solution of propylene carbonate, ethylene carbonate, and fluoroethylene carbonate (volume ratio 1:1:0.05) as the electrolyte;

[0074] ③Battery assembly: It was carried out in a glove box filled with argon (moisture <1ppm), with metal sodium sheets used as auxiliary electrodes and reference electrodes, and glass fiber (Whatman GF / F) used as the diaphragm. After assembly in the mold, it was sealed and allowed to stand at room temperature for 10 hours to obtain a battery sample.

[0075] (1) Charge and discharge test: At room temperature, the battery is cycled using the LAND CT-2001A battery test system; the charge and discharge voltage range is 2.4-4.3V;

[0076] Table 1: Statistical table of electrochemical performance test data of Examples 4-6 and Comparative Examples 3-5

[0077]

[0078] As can be seen from Table 1, the first discharge capacity of the sodium vanadium fluorophosphate sodium ion battery positive electrode material prepared in this application at a rate of 1C is above 119.4 mAh / g, which is close to its theoretical capacity (128.3 mAh / g). Moreover, after 300 cycles, its capacity retention rate reaches 92.4%, showing good cycle performance. At the same time, at a high current density of 10C, the discharge capacity of the sodium vanadium fluorophosphate sodium ion battery positive electrode material prepared in this invention can still reach 110.3 mAh / g, showing its excellent rate performance, which can meet the needs of practical applications of sodium ion batteries.

[0079] The sodium vanadium fluorophosphate sodium ion battery positive electrode material prepared by the present invention has a first discharge specific energy of 446.1 mWh / g at a 1C rate, and a discharge specific energy retention rate of 92.1% after 300 cycles. The energy density value of the sodium vanadium fluorophosphate prepared by the present invention is significantly improved.

[0080] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material, characterized in that: The steps include: S1: Add a carbon source, a vanadium source, deionized water, and a regulator into a reaction bottle and stir once, then add a phosphorus source, a fluorine source, and a sodium source and stir twice to obtain gel A; S2: heating gel A to remove water, vacuum drying, and grinding to obtain a precursor; S3: pre-sintering, secondary sintering, and furnace cooling the precursor in an inert gas atmosphere to obtain a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material; The carbon source is oxalic acid; The preparation method of the regulator comprises the following steps: A1: Add calcium lignin sulfonate, deionized water and maleic anhydride into a reaction kettle and disperse them evenly, adjust the pH to 10-11, control the temperature to 60-80°C, keep the reaction for 1-3h, precipitate, wash and dry to obtain component 1; A2: In a nitrogen atmosphere, component 1, thionyl chloride and N,N'-dimethylbenzoyl are added to a reaction bottle and dispersed evenly, refluxed for 18-24 hours, thionyl chloride is removed by vacuum distillation, washed and dried to obtain component 2; A3: In a nitrogen atmosphere, add diethylenetetramine and triethylenetetramine into a reaction bottle, control the temperature at 120-130°C, keep the reaction warm for 24-36 hours, remove triethylenetetramine by vacuum distillation, filter, wash and dry to obtain a regulator.

2. The method for preparing a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material according to claim 1, characterized in that: The addition ratio of calcium lignin sulfonate, deionized water, and maleic anhydride in A1 is 10 g: 100-500 mL: 6-10 g.

3. The method for preparing a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material according to claim 1, characterized in that: The addition ratio of component 1, thionyl chloride and N,N'-dimethylbenzoyl in A2 is 1g:100-200mL:10-20mL.

4. The method for preparing a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material according to claim 1, characterized in that: The addition ratio of diethylenetetramine and triethylenetetramine components in A3 is 1g:20-100mL.

5. The method for preparing a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material according to claim 1, characterized in that: The vanadium source is vanadium pentoxide, sodium metavanadate, and ammonium metavanadate; the carbon source is oxalic acid; the phosphorus source is ammonium dihydrogen phosphate; the sodium source is sodium fluoride; and the fluorine source is sodium fluoride.

6. The method for preparing a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material according to claim 1, characterized in that: The molar ratio of vanadium, phosphorus, fluorine and sodium in gel A is (2-2.5):2:3:(3-6); the molar ratio of the carbon source and the vanadium source is 2-4:1; and the regulator accounts for 1-5% of the total mass of gel A.

7. The method for preparing a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material according to claim 1, characterized in that: The specific steps of the first stirring in S1 are: controlling the temperature at 70-90°C and stirring until a grass green color appears; the specific steps of the second stirring are: controlling the temperature at 80-90°C and stirring until the solution becomes a gel.

8. The method for preparing a sodium vanadium fluorophosphate-based sodium ion battery positive electrode material according to claim 1, characterized in that: The specific steps of pre-sintering in S3 are: controlling the heating rate to 5°C / min, heating to 350-450°C, and pre-sintering for 3-5h; the specific steps of secondary sintering in S3 are: controlling the heating rate to 5°C / min, heating to 700-800°C, and secondary sintering for 4-8h.

9. A sodium vanadium fluorophosphate-based sodium ion battery positive electrode material, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for preparing modified lignosulfonate

    CN102093573A

  • Battery electrode and non-aqueous solvent-based secondary battery using thereof

    JP1998079252A